2023
DOI: 10.1097/shk.0000000000002104
|View full text |Cite
|
Sign up to set email alerts
|

Low Dose of Esmolol Attenuates Sepsis-Induced Immunosuppression via Modulating T-Lymphocyte Apoptosis and Differentiation

Abstract: Background: Immunosuppression caused by immune cell apoptosis and an imbalance of T helper 2 cells (T H 2) and T helper 1 cells (T H 1), is associated with poor outcomes in septic patients. Esmolol was reported to improve survival by modulating immune responses in septic shock. Whether esmolol could alleviate sepsis-induced immunosuppression and the optimal dose are unclear. Methods: Four hours after cecal ligation and puncture (CL… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…PPI network analyzed for the intersection genes and showed that adaptive immunity genes formed a prominent cluster, mainly composing to sepsis [2,8] . Our study was quite in consensus with the suggestions as demonstrated by the fact that the MEblue module significantly associated with sepsis shock and was enriched with downregulated genes for antigen processing and presentation, and type 1 and type 2 helper T cell differentiation [9][10][11] , which exhibited inhibition of T cell activation and differentiation. Besides, the MEblue module was enriched with decreased hematopoietic cell lineage genes including CD2, CD5 and CD7 markers for T-cell progenitors, which meant competence of primitive Hematopoietic Stem Cell (HSC) to produce T lymphocytes might be severely compromised in sepsis shock patients.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…PPI network analyzed for the intersection genes and showed that adaptive immunity genes formed a prominent cluster, mainly composing to sepsis [2,8] . Our study was quite in consensus with the suggestions as demonstrated by the fact that the MEblue module significantly associated with sepsis shock and was enriched with downregulated genes for antigen processing and presentation, and type 1 and type 2 helper T cell differentiation [9][10][11] , which exhibited inhibition of T cell activation and differentiation. Besides, the MEblue module was enriched with decreased hematopoietic cell lineage genes including CD2, CD5 and CD7 markers for T-cell progenitors, which meant competence of primitive Hematopoietic Stem Cell (HSC) to produce T lymphocytes might be severely compromised in sepsis shock patients.…”
Section: Resultssupporting
confidence: 89%
“…In steady-state, HSC was kept in a cell and Th17 differentiation. Our study suggested that HSCs defective derived T-cells might be the predominant reason for T-cell number reduction, despite sepsis shock it also induces apoptosis or any other unfavourable conditions as reported [10,32] . A clinical study had documented that lymphopenia and T-cell depletion were critically associated with increased mortality.…”
Section: Resultssupporting
confidence: 52%
“…Abnormal differentiation of T lymphocytes may lead to the pathogenesis of sepsis [21]. Ma et al [22] found that low-dose esmolol alleviates sepsis-induced immune suppression by regulating T lymphocyte apoptosis and differentiation. The process of white blood cells extravasating from the bloodstream to inflamed tissues requires adhesion between white blood cells and endothelial cells, allowing white blood cells to locate infected or damaged tissues and participate in pathogen clearance, repair, and regeneration processes [23].…”
Section: Discussionmentioning
confidence: 99%
“…The apoptosis rate of T cells shows an obvious increase in sepsis, and inhibition of apoptosis alleviates the severity of sepsis. 19 , 20 The exhaustion of T cells is also closely related to the mortality of sepsis patients. 10 , 21 , 22 HLA-DR is a class II major histocompatibility complex (MHC) protein that mediates antigen-specific recognition by CD4+ helper T lymphocytes.…”
Section: Discussionmentioning
confidence: 99%